Data for project "Cracks in the painting Konstnärsförbundets Styrelse", RAÄ-2021-3125 - Berg, Helena; Canosa, Elyse (Swedish National Heritage Board, 2024)
Data from the project "Cracks in the painting Konstnärsförbundets Styrelse" (Diarienummer RAÄ-2021-3125) including files for sample descriptions. Data from the following analytical techniques is included:

Scanning electron microscopy with energy dispersive x-ray spectroscopy (SEM-EDS);

X-ray fluorescence spectroscopy (XRF);

X-ray imaging;

Technical photography;

Microscopy.

Instrument reports including technical specifications of each instrument as well as a sampling protocol can be found under DOI 10.5281/zenodo.10560902. All data was collected as part of the bachelor thesis "Sprickorna i Konstnärsförbundets styrelse" by Helena Berg, Department for Conservation, University of Gothenburg (https://hdl.handle.net/2077/72659).
Keywords: Heritage Science; RAÄ-2021-3125; Paintings conservation; Konstnärsförbundets styrelse; Scanning electron microscopy; X-ray fluorescence spectroscopy; Technical photography; Nationalmuseum; Richard Bergh; History and Archaeology; Historia och arkeologi